UNDERSTANDINGS AND EXPRESSIONS ABOUT THE QUOTA SYSTEM AS AFFIRMATIVE POLICY ACTION BY HIGH SCHOOL STUDENTS - Francisca Lamarão, Isabel; Couto Monteiro, Stéfano; Regina Zasso, Carla (Revista Gênero e Interdisciplinaridade, 2024)
This article deals with the understanding of high school students about the right to racial and social quotas as a public policy that allows the rise of socially disadvantaged populations to higher education. It is the result of research carried out with students from 3rd year high school classes at Colégio Estadual Professora Terezinha Scaramussa (CEPTS), located in the city of Santa Cruz Cabrália, state of Bahia. Data were obtained through the application of a didactic sequence involving exposition, a questionnaire with mixed questions – open and multiple choice, associated with an individual textual production. Based on the data analysis, the perspectives of content analysis were considered and, in a preliminary manner, it is possible to understand that it is necessary to promote differentiated and continuous strategies so that students are clear about the importance of appropriating public policies in their daily lives and, in this case more specifically, about racial and social quotas, as well as realizing that the observance of discursive practices about racial and social quotas in the subjects that make up the curriculum is not yet common in schools.